APLIKASI CHATBOT PERSEWAAN KOST BERBASIS WEB MENGGUNAKAN METODE WATERFALL - Dicky Bagas Oktaviandia; Saiful Ulya; Achmad Ridwan; Avira Budianita (Universitas Muhammadiyah Kudus, 2023)
The growth of boarding houses is currently increasing, forcing boarding owners to do various ways to offer their business. The limited availability of information regarding the location, facilities, and costs of the boarding house makes prospective boarding house tenants do not have relevant information, so they become disinterested. As in Pak Purwanto's boarding house, one of them is marketing, which is still done manually, which makes most prospective boarding house tenants not aware of this information because it is not widely spread. Therefore, the purpose of this research is to build a web-based boarding chatbot application using the waterfall method (case study: kost pak purwanto) to make marketing more effective and efficient. Data collection was carried out in several ways, namely literature study, observation, and interviews. The results obtained in this study after going through the implementation and testing stages with the black box testing method produce a computerized system with artificial intelligence technology in the chatbot that can answer questions from prospective boarding house tenants so that this system becomes better, more effective and efficient than the previous system which was still manuals. The existence of this system makes it easier for boarding house owners to market their boarding houses so that they can develop more and become more well-known. Keywords: Information systems, Applications, Artificial intelligence, Chatbots, Boarding houses, Waterfall, Black box testing.